(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The “value” of a discipline, occasionally arouses debate. With History it’s no different, and sometimes perhaps more challenging. As the general trend still indicates declining numbers in most provinces, Westerford High School in Cape Town displays an outstanding example of an institution with high success rates in History. From the Westerford High experience other schools are challenged to reconsider their status in the teaching of History and adapt where it is required. A personal view on why perhaps Westerford’s success in History is exchanged.